Pemaknaan Revolusi Mental dalam Al-Qur’an Perspektif Tafsir Al-Misbah - Sarmadan Hasdiansyah; Muthoharoh; Helmalia; Irdawati Saputri; Fitriani (Gunung Djati Conference Series, 2022)
This study examines the mental revolution in the Qur'an from the perspective of al-Misbah interpretation. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the study of the verses of the Qur'an in the interpretation of al-Misbah, while the material object of this research is the mental revolution for the Indonesian context. The results of research and discussion show that the Qur'an does not have a detailed term regarding mental revolution, this according to the interpretation of al-Misbah can be understood in terms of the change from darkness to light. This study concludes that a mental revolution in the Al-Quran afsir al-Misbah perspective can occur when Allah wills and humans are determined and try to change themselves for the benefit of society at large.